Incorporating thesaurus in searching relevant ayat from the translated Al-Quran / Wan Iznif Wan Ibrahim - Wan Ibrahim, Wan Iznif (2002)
This project incorporates the Rules Application Order (RAO) stemming algorithm with thesaurus approach by Rapizal. It is an opportunity to find out whether combining stemming with thesaurus will improve retrieval effectiveness and efficiency. Advances in information technology has made it possible for a wide range of text-based information to be searched and retrieved, online, locally or from remote hosts. A wide range of text-based information is searched and retrieved from online connection to remote hosts or locally. This type of popularity is due to advancement in technology that is rapidly growing from day to day 3 There are many Malay word variants that have the same meaning available from Malay words. In order to overcome these word variant problems, the development of a computational technique that could transform both user's search and database words into a single canonical form that is known as Conflation is introduced. One of the well-known conflation algorithms, stemming, is only used to identify morphological variants. Stemming algorithms are language dependent. They have proven to be successful in reducing words with the same stem to a common form and are evidenced by the work of many researchers. Unfortunately, the conflation method is unable to conflate different words that possess the same meaning. These words can only be conflated by a thesaurus that can handle hierarchic, synonymic, and also morphological relationship. To create a thesaurus for a given subject an extensive manual and highly skilled so to solve this problem, another language dependent conflation method, thesaurus is used. It can build all types of relationships that exists between words. The information retrieval thesaurus typically contains a list of terms, where a term is either a single word or phrase. The relationships between them are also included to assist in coordinating indexing and retrieval. So it is found that the incorporation of stemming algorithm and thesaurus successfully increase the retrieved and relevant documents using Malay query words.